APPLICATION OF FUZZY LOGIC IN AUTOMATIC COOLING COMPUTER DESIGN USING PELTIER BASED ON ATMEGA328 MICROCONTROLLER - Rizky Pratama Putra; Rakhmat Kurniawan R; Abdul Halim Hasugian (Sean Institute, 2021)
Slow or lag computer problems can be caused by overheating of computer hardware such as the processor, if the computer overheats it will reduce the performance of the processor performance. In general, computers are equipped with coolers such as air cooling to avoid overheating, but for heavy and intensive work, air cooling is still not effective in cooling computer processors, so in this study an automatic computer cooling device was created that was effective in cooling computers. This tool uses a peltier to cool the coolant that flows on the cold side of the peltier. To control the Peltier, fuzzy logic is applied to control the temperature of the computer processor. This fuzzy logic will be embedded into the microcontroller. Cold generated based on the information provided by the computer to the microcontroller via serial communication. Based on the benchmark test, the average Core1 Temperature is 26.75oC, Core2 Temperature is 25.25oC and Package Temperature is 29oC using water cooling Peltier with fuzzy logic, while with water cooling the average Core1 Temperature is 33.5oC, Core2 Temperature is 33oC and Package Temperature is 35.25oC and with The average water cooling radiator has a Core1 temperature of 32.25oC, a Core2 temperature of 31.5oC and a Package Temperature of 34.25oC before performing the benchmark test. When the benchmark test runs, the average Core1 Temperature is 52.25oC, Core2 Temperature is 51oC and Package Temperature is 54.25oC using water cooling Peltier with fuzzy logic, while with water cooling the average TemperatureCore1 is 65oC, Core2Temperature is 64.25oC and PackageTemp is 67.25oC as well as with water The average cooling radiator temperature is Core1 57oC, Core2 Temperature 59oC and Package Temperature 59.25oC with an average room temperature of 30oC during the test. From the test results by comparing the tools in this study, water cooling Peltier with fuzzy logic is better and more effective in cooling computer processors. Keywords: Computer Cooling, Fuzzy Logic, Microcontroller